2009
DOI: 10.1093/alcalc/agp081
|View full text |Cite
|
Sign up to set email alerts
|

Planned and Unplanned Discharge from Alcohol Services in Scotland, 2004-2008

Abstract: More than one of every two entries to alcohol misuse services between 2004 and 2008 resulted in an unplanned discharge. The trend of improvement over the examined 4-year period was not consistent for all regions. A comparison of this figure with available US and Welsh data is made. The importance of these data in assessing the cost-effectiveness of alcohol treatment services and implications for policy making is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Primary care facilities as entry point seem pragmatic, yet Nadkarni et al [ 35 ] reported a low consent rate of 23% next to a high dropout rate, which was not the case for the Treatment Camp approach with a consent rate of 89% and no dropouts during the Treatment Camp intervention. The low dropout-rate during treatment in the present study is exceptional for this patient-group [ 63 ].…”
Section: Discussionmentioning
confidence: 88%
“…Primary care facilities as entry point seem pragmatic, yet Nadkarni et al [ 35 ] reported a low consent rate of 23% next to a high dropout rate, which was not the case for the Treatment Camp approach with a consent rate of 89% and no dropouts during the Treatment Camp intervention. The low dropout-rate during treatment in the present study is exceptional for this patient-group [ 63 ].…”
Section: Discussionmentioning
confidence: 88%
“…Alcohol dependence is a major global public health problem which affects 5.1% of the global population and causes up to 3.3 million deaths per year, the majority of those being related to cardiovascular diseases [ 1 ]. Although integrative multimodal acute and rehabilitative treatment regimens have been widely established to reduce the disease burden related to alcohol dependence, malcompliance and low rates of adherence to treatment are frequently compromising success of these therapies [ 2 , 3 ]. Moreover, even after completion of rehabilitation relapse poses a major problem.…”
Section: Introductionmentioning
confidence: 99%
“…Though many factors influence continuation in treatment, these previous studies indicate that recording treatment completion is a useful predictor for progress beyond treatment. Rates of treatment noncompletion in alcohol treatment services vary remarkably in available data, from more than 50% in Scotland to approximately 10% to 20% over several years in inpatient rehabilitation programs in Germany, and are in general lower in alcohol-dependent individuals compared to participants with a substance use disorder 4,16–20…”
Section: Introductionmentioning
confidence: 99%